Mapping selfies and memes as Touch - Andreallo, Fiona (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book offers a rich and nuanced analysis of digitally networked socialities as culturally meaningful relationships of Touch. Focusing on the ways Touch is practised in everyday social interactions serves as a basis for understanding how Touch is multiply significant - physically, emotionally, intellectually and politically. Fiona Andreallo initiates a map of the fundamentals of Touch and how they can be considered for future research in considering digitally networked cultures. This map also serves as a basis for closely examining selfies and memes. Andreallo focuses on a specific example of the PrettyGirlsUglyFaces meme and ugly selfies (uglies) and explores how memes and selfies are mapped as Touch involving textures of both intimacy and violence. Andreallo also discusses technological seamlessness and cultural semefulness as conversations on the social relationships of Touch, and proposes the term "semeful sociabilities" to describe how the everyday technological self engages in practices of Touch. This book is a compact and approachable insight into selfies and memes as everyday culturally networked Touch relationships, and offers a way forward in recognising technological relationships as culturally meaningful. Fiona Andreallo is a Postdoctoral, Early Career fellow in Design and Social Context at RMIT University, Australia. She is also an Honorary Research Associate in Media and Communications at The University of Sydney, Australia. Fiona's research focuses on human-technological relationships, communication and cu ltures. She has previously published in areas of social media, social robotics and technological relationships towards personalised care. Her research approach is shaped by her background as a digital media artist. In her research, she has worked with prominent stakeholders, including local government, art galleries, private care companies, and The Sydney Institute for Robotics and Information Systems (SIRIS). .